Union Army Veterans, All Grown Up - Costa, Dora L. (Hist Methods, 2017)
This paper overviews the research opportunities made possible by a NIA-funded program project, Early Indicators, Intergenerational Processes, and Aging. Data collection began almost three decades ago on 40,000 soldiers from the Union Army in the US Civil War. The sample contains extensive demographic, economic, and medical data from childhood to death. In recent years, a large sample of African-American soldiers and an oversampling of soldiers from major US cities have been added. Hundreds of historical maps containing public health data have been geocoded to place soldiers and their family members in a geospatial context. With newly granted funding, thousands of veterans will be linked to the demographic information available from the census and vital records of their children.